New report of Laophonte cornuta Philippi,1840 (Copepoda: Harpacticoida) from the coral area, North of Tioman Island, South China Sea - Sham, Azrina; Kassim, Zaleha; Ahmad, Zuhairi; Ismail, Ahmad (Universiti Teknologi Malaysia, 2020)
Laophonte cornuta Philippi 1840 was first reported in rather temperate regions and later noted to extend their distribution to the warmer coasts. The earlier reports were based on specimen collected from bottom vegetation or sediment enriched in organic matter. The present study was carried out during the warm month phenomenon which struck coral areas in the South China Sea in 2016. Sediment core samples were collected by SCUBA divers in the coral areas at Pulau Tulai (2°54'24.84"N,104° 5'57.67"E) and Batu Malang (2°52'29.98"N,104° 8'47.92"E), in the northern part of Tioman Island. The bottom substrates were covered by mostly dead corals and coral rubbles. Taxonomic observation was carried out following the sorting and microscopic dissection process in the laboratory. The denticulate margin of somites along with blunt short spinules distributed on the surface as shown from the Scanning Electroscopic Microscopy (SEM) observation proves their morphological adaptation to survive between the coral rubbles and gravels in the study area. Other variation found is on the size of the caudal rami which is very much slender than those reported from colder regions. Except for the setae formula, it shared similar characters with L. paradduensis reported from Maldivesand L. aeutirostris from Monterey Bay. The present specimen also shared some variation found in specimen reported from the Andaman Sea. L. cornuta reported from the Tioman Island might be able to endure the harsh environment due to their robust feature of the body surface.